Immediate tooth replantation in rats: effect of systemic antibiotic therapy with amoxicillin and tetracycline - Melo, Moriel Evangelista [UNESP]; Silva, Cristina Antoniali [UNESP]; Gomes, Weglis Dyanne de Souza [UNESP]; Silva, Vanessa Ferreira da [UNESP]; Brandini, Daniela Atili [UNESP]; Poi, Wilson Roberto [UNESP]; Castilho, Lithiene Ribeiro [UNESP]; Sonoda, Celso Koogi [UNESP]; Barioni, Sônia Regina Panzarini [UNESP] (Springer, 2015)
The aim of this study was to evaluate the influence of systemic administration of antibiotics (amoxicillin and tetracycline) at the different phases of the repair process (7, 15, 30 days) in immediate rat tooth replantation. Ninety rats had their incisors extracted and stored in saline for 5 min. Next, the teeth were replanted, and the animals were assigned to three groups according to the antibiotic administered by oral gavage: control group, amoxycillin group, and tetracycline group. Euthanasia was performed at 7, 15, and 30 days after replantation. Regardless of the evaluation period, the connective tissue underlying the epithelial attachment and the periodontal ligament showed statistically significant difference relative to the acute inflammatory infiltrate, which was more intense in the control group followed by the tetracycline group. These results point to the fact that systemic antibiotic therapy (SAT) in immediate tooth replantation is beneficial to pulpal and periodontal ligament repair and that amoxycillin is an excellent option. There is a lack of randomized studies assessing how the use of systemic antibiotics could influence tooth healing after immediate replantation.
Keywords: Root resorption; Immediate tooth replantation; Amoxycillin; Tetracycline